Philosophy of religion : selected readings - Peterson,michael(Editor) Hasker,William(Editor) Reichenbach,Bruce(Editor) Basinger,David(Editor) (Oxford University Press, 1996)
This excellent anthology in the philosophy of religion examines the basic classical and a host of contemporary issues in thirteen thematic sections. Assuming little or no familiarity with the religious concepts it addresses, it provides a well-balanced and accessible approach to the field.